2009
DOI: 10.1097/psy.0b013e31819b6a08
|View full text |Cite
|
Sign up to set email alerts
|

Anger Expression and Sleep Quality in Patients With Coronary Heart Disease: Findings From the Heart and Soul Study

Abstract: Objective-To evaluate if anger expression affects sleep quality in patients with coronary heart disease (CHD). Research has indicated that poor sleep quality independently predicts adverse outcomes in patients with CHD. Risk factors for poor sleep quality include older age, socioeconomic factors, medical comorbidities, lack of exercise, and depression.Methods-We sought to examine the association of anger expression with sleep quality in 1020 outpatients with CHD from the Heart and Soul Study. We assessed anger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 64 publications
0
31
0
3
Order By: Relevance
“…However, we note that insomnia is currently defined based on self-report, 50 and that single-item measures of sleep and physical activity have previously been associated with important psychological and medical outcomes. 4,39 In particular, self-reported measures of sleep and physical activity have been predictors of metabolic syndrome 15 and cardiovascular events 4 in previous studies. Nonetheless, we recommend that future research include longer and/or more frequent subjective assessments as well as objective assessments to examine physiological correlates of sleep quality and physical activity (i.e., objective measurement of fitness).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we note that insomnia is currently defined based on self-report, 50 and that single-item measures of sleep and physical activity have previously been associated with important psychological and medical outcomes. 4,39 In particular, self-reported measures of sleep and physical activity have been predictors of metabolic syndrome 15 and cardiovascular events 4 in previous studies. Nonetheless, we recommend that future research include longer and/or more frequent subjective assessments as well as objective assessments to examine physiological correlates of sleep quality and physical activity (i.e., objective measurement of fitness).…”
Section: Discussionmentioning
confidence: 99%
“…37 A question assessing sleep quality has been recommended as essential when assessing sleep by self-report, 38 and the particular sleep quality question used in the present study has previously predicted outcomes such as anger expression. 39 …”
Section: Sleepmentioning
confidence: 99%
“…In addition, suppressed anger has also been identified as a contributing factor in poor sleep quality among patients with coronary heart disease. 30 Perhaps more so than other psychosocial factors, the role of anger and hostility among women appears to be different for men and women. In a review of psychosocial factors in the development of CHD in women, Low and colleagues 31 identified that hostility was less consistently associated with CHD among women as opposed to men.…”
Section: Anxietymentioning
confidence: 99%
“…((1) very bad to (5) very good), thereby, providing self-report measures of time in bed, duration, sleep onset latency, and sleep quality, respectively. These single-item sleep measures are common in epidemiologic studies and have been linked to a variety of negative health outcomes [24][25][26][27]. Finally, participants were asked if their sleep patterns over the past week represent their typical sleep pattern over the past 3 months (typical versus atypical).…”
Section: Sleep Measuresmentioning
confidence: 99%